Challenges in Tracking Non- Punched but Worked Hours: A Deep Dive into Travel and Training Time - Manikam, Karthikeyan (Human Resource and Leadership Journal, 2023)
Purpose: This paper presents a comprehensive study on the challenges of tracking non-punched but worked hours, with a particular focus on travel and training time. These unregistered hours pose significant challenges in the realms of employee compensation and labor law compliance. Standard time-tracking systems are not equipped to handle the nuances of such non-traditional work hours, leading to potential disputes and financial grievances. Methodology: Using travel time as a case study, this paper discusses the multifaceted nature of the problem, including unpredictability in travel, compensation for unexpected delays, and the inadequacies of current systems to automatically recognize and adjust for these hours. We propose a solution utilizing a customized program within the Kronos Time and Attendance system to accurately categorize and calculate non-punched hours, ensuring fair compensation and compliance with labor regulations. Findings: The implications of these findings are profound, highlighting the necessity for advanced tracking solutions that align with labor laws while upholding fairness and transparency. Unique contribution to theory, practice and policy: This paper aims to drive a paradigm shift towards integrating sophisticated time-tracking systems that respect and acknowledge every aspect of an employee's work life.